Advisory Opinion OC-32/25 of May 29, 2025 requested by the Republic of Chile and the Republic of Colombia — Climate Emergency and Human Rights. - Corte Interamericana de Derechos Humanos (2025)
On May 29, 2025, the Inter-American Court of Human Rights (hereinafter “the Court” or “the Tribunal”) issued an Advisory Opinion in response to the request submitted by the Republic of Chile and the Republic of Colombia on “Climate Emergency and Human Rights.”